2004
DOI: 10.1016/s0002-9440(10)63260-9
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Expression of Two Paracrine Melanogenic Cytokines, Stem Cell Factor and Endothelin-1, in Ultraviolet B-Induced Human Melanogenesis

Abstract: Stem cell factor (SCF) and endothelin-1 (ET-1) have been reported to be up-regulated at the protein and gene levels in human epidermis after ultraviolet B (UVB) irradiation and to play central roles in UVBinduced pigmentation. However, little is known about the time sequence of SCF and ET-1 expression in UVB-exposed human epidermis and the coordination of their roles during epidermal pigmentation. To clarify such parameters in UVB-exposed human skin, we measured the expression patterns of SCF and ET-1 (as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
130
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(142 citation statements)
references
References 75 publications
(73 reference statements)
5
130
1
2
Order By: Relevance
“…The mechanism of epidermal hyper-pigmentation occurs by the increased expression level of ET-1 and SCF, or the decreased expression of TNF-α and IL-6. In particular, SCF and ET-1 are germane to the hyper-pigmentary mechanism by UVB-induced melanin synthesis [26][27][28][29][30]. Presently, GAE inhibited SCF-stimulated pigmentation in human epidermal equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of epidermal hyper-pigmentation occurs by the increased expression level of ET-1 and SCF, or the decreased expression of TNF-α and IL-6. In particular, SCF and ET-1 are germane to the hyper-pigmentary mechanism by UVB-induced melanin synthesis [26][27][28][29][30]. Presently, GAE inhibited SCF-stimulated pigmentation in human epidermal equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent visualization was performed and normalized against a control protein, ␤-actin (Sigma) as described elsewhere. 59 …”
Section: Western Blottingmentioning
confidence: 99%
“…5 In addition, prostaglandins (PGs) are key mediators of diverse functions in the skin; and several reports 6,7 have suggested that PGs mediate postinflammatory pigmentary changes by modulating melanin synthesis and melanocyte dendricity.…”
mentioning
confidence: 99%
“…[2][3][4] The two main paracrine melanogenic cytokines, stem cell factor (SCF) and endothelin (ET)-1, have been demonstrated to play pivotal roles in skin pigmentation, including UV-Binduced pigmentation. 5 In addition, prostaglandins (PGs) are key mediators of diverse functions in the skin; and several reports 6,7 have suggested that PGs mediate postinflammatory pigmentary changes by modulating melanin synthesis and melanocyte dendricity.…”
mentioning
confidence: 99%
See 1 more Smart Citation